2014
DOI: 10.1111/cen.12655
|View full text |Cite|
|
Sign up to set email alerts
|

Adrenal responses to a low‐dose short synacthen test in children with asthma

Abstract: SummaryObjectives Corticosteroids are known to cause adrenal suppression. The aim of this study was to assess clinical factors affecting responses to a low dose short synacthen test (LDSST) in asthmatic children using corticosteroids. Design Patients were recruited from secondary care paediatric asthma populations within the UK. Patients Asthmatic children (5-18 years), receiving corticosteroids, underwent a LDSST (n = 525). Measurements Demographics and corticosteroid doses were tested for association with ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…The SSTs are attractive tests of adrenal reserve in children as the safety profile is excellent and tests are well tolerated 8. Two doses are used most commonly: standard (250 µg, standard dose short Synacthen test (SDSST)) and low (1 µg, low dose short Synacthen test (LDSST)) doses, adjusted variably for body size according to local protocols.…”
Section: Diagnostic Tests Of Adrenal Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSTs are attractive tests of adrenal reserve in children as the safety profile is excellent and tests are well tolerated 8. Two doses are used most commonly: standard (250 µg, standard dose short Synacthen test (SDSST)) and low (1 µg, low dose short Synacthen test (LDSST)) doses, adjusted variably for body size according to local protocols.…”
Section: Diagnostic Tests Of Adrenal Functionmentioning
confidence: 99%
“…The LDSST is a safe test, associated with few side effects,8 and it is for this test that normative data in children have been collected. Data from 33 short, normal children report that a peak cortisol value of 500 nmol/L gives a false positive rate as high as 21%, with median cortisol concentrations being 633 nmol/L, range 417–1052 30.…”
Section: Diagnostic Tests Of Adrenal Functionmentioning
confidence: 99%
“…Following the recent publication of the above article in volume 82, issue 5 of Clinical Endocrinology , the authors have requested the inclusion of the following to the Acknowledgement section “This research was supported by the National Institute for Health Research Biomedical Research Centre at Great Ormond Street Hospital for Children NHS Foundation Trust and University College London.”…”
mentioning
confidence: 99%
“…The risks of adrenal suppression with inhaled GCs have previously been highlighted, for example, a UK survey of adult endocrinologists and paediatricians identified a number of cases of ‘acute adrenal crisis’ in individuals with asthma treated with inhaled GCs, and the relatively low response rate (24%) in this study may have resulted in an underestimation of the true incidence 1. A more recent study reported that 37% of children with asthma had a peak cortisol level below the accepted threshold for biochemical normality following a low dose short synacthen test and suggested that children with asthma taking any preparation of inhaled GCs at any dose may be at risk of adrenal suppression4—that is, it is not only children on ‘excessive’ doses of inhaled GCs who are at risk.…”
mentioning
confidence: 60%